Exploring SME investment patterns in Ireland: New survey evidence - Gargan, Eric; Lawless, Martina; Martinez-Cillero, Maria; O'Toole, Conor (ESRI, 2018)
Research uses new survey data to address knowledge gaps around the investment activity of small Irish companies.